2010
DOI: 10.1007/s10059-010-0122-z
|View full text |Cite|
|
Sign up to set email alerts
|

The Neural Stem Cell Fate Determinant TLX Promotes Tumorigenesis and Genesis of Cells Resembling Glioma Stem Cells

Abstract: A growing body of evidence indicates that deregulation of stem cell fate determinants is a hallmark of many types of malignancies. The neural stem cell fate determinant TLX plays a pivotal role in neurogenesis in the adult brain by maintaining neural stem cells. Here, we report a tumorigenic role of TLX in brain tumor initiation and progression. Increased TLX expression was observed in a number of glioma cells and glioma stem cells, and correlated with poor survival of patients with gliomas. Ectopic expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 27 publications
1
40
0
Order By: Relevance
“…Overexpression of TLX in NSCs or glial cells is sufficient to sensitize them to tumorigenesis under either a p53 Ϫ/Ϫ or Ink4a/ Arf Ϫ/Ϫ genetic background (18,28). This implicates TLX as a potential therapeutic target against gliomas (18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overexpression of TLX in NSCs or glial cells is sufficient to sensitize them to tumorigenesis under either a p53 Ϫ/Ϫ or Ink4a/ Arf Ϫ/Ϫ genetic background (18,28). This implicates TLX as a potential therapeutic target against gliomas (18).…”
Section: Discussionmentioning
confidence: 99%
“…1 and 7), lending to its use as a diagnostic biomarker (18,28,30,34,42). Future experiments are warranted to tease out the signaling path- .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, elevated expression of TLX has been reported in various types of human glioma [68][69][70][71][72][73] and glioma cell lines [74], and TLX overexpression seems to be associated with a poor prognosis for patients with glioma [74]. A recent study further reported that TLX promotes the progression of neuroblastoma and is correlated with poor survival [56].…”
Section: Tlx and Human Diseasesmentioning
confidence: 99%
“…TLX also promotes neural stem cell self-renewal by down-regulating the expression of cell cycle check genes such as PTEN and p21 (Zhang et al 2006;Sun et al 2007). Elevated expression of TLX has also been implicated in gliomagenesis, making it a promising therapeutic target for the treatment of human brain tumors (Liu et al 2010;Park et al 2010;Zou et al 2012;Xie et al 2014). A number of corepressors of TLX have been identified, which include Atrophin proteins, LSD1 (lysine-specific demethylase), and histone deacetylases (HDACs) (Wang et al 2006;Sun et al 2007Sun et al , 2010Yokoyama et al 2008), among which Atrophin proteins are directly recruited by TLX.…”
mentioning
confidence: 99%